2006
DOI: 10.1017/s1461145705006401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute topiramate dosing on methamphetamine-induced subjective mood

Abstract: Clinical studies have shown that topiramate, a sulphamate-substituted fructopyranose derivative, might be an efficacious treatment for alcohol dependence, smoking cessation within an alcohol-dependent population, and cocaine dependence. Mechanistically, topiramate's therapeutic effects have been hypothesized to be due to inhibition of cortico-mesolimbic dopamine function, the primary substrate that governs the acquisition, maintenance, and reinstatement of goal-directed behaviour towards seeking abused drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Indeed, drowsiness experienced by the topiramate group may have contributed to this perception. This proposed mechanism for enhanced rewarding effects is consistent with the previous study on topiramate interactions with methamphetamine (Johnson et al 2006). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, drowsiness experienced by the topiramate group may have contributed to this perception. This proposed mechanism for enhanced rewarding effects is consistent with the previous study on topiramate interactions with methamphetamine (Johnson et al 2006). …”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with a recent report that acute topiramate treatment (25 and 50 mg) enhanced the subjective strength and rewarding effects of intravenous nicotine (0.5 and 1.0 mg/kg) (Sofuoglu et al 2006). Studies on methamphetamine found similar results in which intravenous methamphetamine-induced (15 and 30 mg) ratings of euphoria and stimulation were enhanced by topiramate (100 and 200 mg) pretreatment (Johnson et al 2006). This latter study also found evidence that topiramate reduced positive subjective mood (Johnson et al 2006), similar with the present finding that topiramate produced an overall increase in symptoms of nicotine withdrawal.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Topiramate a GABA agonist/AMPA antagonist medication was tested in an interaction study with methamphetamine which showed that topiramate enhanced some of the positive effects of methamphetamine. This was attributed to possible PK interaction on methamphetamine metabolism (Johnson et al 2007). A multisite outpatient trial of topiramate 200 mg for reducing meth use was negative for the primary outcome.…”
Section: Gaba Agonistsmentioning
confidence: 99%
“…Epigenetic promoter methylation, especially of the p16 gene, due to tobacco smoking has been suggested to be one important pathway in the pathogenesis of lung cancer (Kim et al, 2001;von Zeidler et al, 2004;Dammann et al, 2005). Changes in specific promoter methylation have also been suspected to be associated with tobacco smoking and with a poor prognosis in lung cancer (Kikuchi et al, 2006;Johnson et al, 2006). In addition, an association of lung cancer with global DNA methylation has been found (Piyathilake et al, 2001).…”
Section: Introductionmentioning
confidence: 99%